A Complex Paleo‐Surface Revealed by the Yutu‐2 Rover at the Lunar Farside. Issue 20 (20th October 2021) - Lai, Jialong; Xu, Yi; Bugiolacchi, Roberto; Wong, Hon Kuan; Xu, Luyuan; Zhang, Xunyu; Zhang, Ling; Zhang, Xiaoping; Xiao, Long; Liu, Bin; Di, Kaichang
Abstract: The observable lunar surface is represented by a ubiquitous layer of fine‐grained materials produced by billions of years of hypervelocity pounding of its crustal layer. The data from the Lunar Penetrating Radar onboard Chang'e‐4 (CE‐4) rover (Yutu‐2), which is exploring the Von Kármán Crater on the lunar farside, are helping to peel back the upper layer of finely comminuted materials, interpreted as a thick layer of ejecta from the neighboring Finsen crater, to reveal a complex paleo‐surface morphology. During the rover's 560 m journey, from depths of 7–20 m, distinct variations in the returned signal characteristics reveal a possible 270 ± 10 m buried crater with an estimated age of less than 100 m.y. A smooth surface depression that lies to the southwest of the Yutu‐2 rover's travel path might not be the remnant of a degraded crater but a related surface expression of the hidden structure. Plain Language Summary: The absence of an atmosphere and substantial resurfacing events in the last couple of billion years means that the Moon's surface has journeyed through space exposed to anything that travels through it and, unlike the Earth, most of these "encounters" have left a mark. Thus, the good news for scientists is that the lunar surface represents a record of astrophysical phenomena within the Solar System that is no longer available on its larger companion: our planet. However, the larger impacts have indeed contributed to modify its surface hiding some of its old terrains. The Lunar Penetrating Radar (LPR) onboard Chang'e‐4 (CE‐4) rover (Yutu‐2) can see below the surface as it makes its way across the lunar ground, revealing the ancient lunar surface (paleo‐surface) at the depth of ∼12 m. It has mapped its elevation profile, which now we can see that it has been substantially modified following its formation some 3.1 billion years ago. Notably, the LPR has discovered a 270 m sized buried crater corresponding to a large ground depression seen on the surface, a first achievement for lunar radar sounding. Key Points: The CE‐4 LPR reveals the paleo‐surface of the lunar farside at a depth between 7 and 20 m The LPR has mapped a 270 m sized buried crater probably related to a larger circular depression on the lunar surface The geomorphology, the subsurface structure, the impact melt deposits, and the exposure time of the buried crater, are analyzed